2019
DOI: 10.1016/j.molimm.2018.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Production of spliced peptides by the proteasome

Abstract: CD8 cytolytic T lymphocytes are essential players of anti-tumor immune responses. On tumors, they recognize peptides of about 8-to-10 amino acids that generally result from the degradation of cellular proteins by the proteasome. Until a decade ago, these peptides were thought to solely correspond to linear fragments of proteins that were liberated after the hydrolysis of the peptide bonds located at their extremities. However, several examples of peptides containing two fragments originally distant in the prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 68 publications
0
23
0
Order By: Relevance
“…Although evidence suggests that noncontiguous CD8 + T cell epitopes are generated primarily by proteasome-mediated peptide splicing involving transpeptidation ( 75 ), the generation of HIPs remains more of a biochemical mystery to date. The sites of formation of HIPs are also under investigation; this knowledge could shed light on how they are produced.…”
Section: Formation Of Noncontiguous T Cell Epitopesmentioning
confidence: 99%
“…Although evidence suggests that noncontiguous CD8 + T cell epitopes are generated primarily by proteasome-mediated peptide splicing involving transpeptidation ( 75 ), the generation of HIPs remains more of a biochemical mystery to date. The sites of formation of HIPs are also under investigation; this knowledge could shed light on how they are produced.…”
Section: Formation Of Noncontiguous T Cell Epitopesmentioning
confidence: 99%
“…Nevertheless, what applied to non-spliced epitopes also seemed to be valid for spliced HLA class I epitopes generated in vitro by PCPS. Thus, FGF-5, SP110, and several gp100-derived spliced epitopes that are recognized by CD8 + T cells on the cell surface were demonstrated to be produced also in in vitro PCPS assays ( Ebstein et al, 2016 ; Vigneron et al, 2019 ). Although in these cases the generation efficiency of spliced epitopes in in vitro PCPS assays seemed to be in line with the in vivo situation, it should be noted, however, that the abundance of spliced epitopes presented at the cell surface is a matter of substantial controversy ( Liepe et al, 2016 ; Liepe et al, 2019 ; Mylonas et al, 2018 ; Paes et al, 2019 ; Rolfs et al, 2019 ).…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, in vitro generation of epitopes using purified 20S proteasomes and synthetic polypeptide substrates encompassing the epitope(s) of interest, in combination with mass spectrometric analyses and both in vitro and in vivo CD8 + T cell assays still represent the most frequently used tool to validate the generation of immune relevant non-spliced peptides, assuming that it closely simulates the in vivo (in cellulo) situation with respect to both quality and relative amounts of the epitope (Kessler et al, 2001;Kessler & Melief, 2007;Sijts & Kloetzel, 2011). Thus, FGF-5, SP110 and several gp100 derived spliced epitopes that are recognized by CD8 + T cells on the cell surface were demonstrated to be produced also in in vitro PCPS assays (Ebstein et al, 2016;Vigneron et al, 2019). Although in these cases the generation efficiency of spliced epitopes in in vitro PCPS assays seemed to be in line with the in vivo situation, it should be noted, however, that the abundance of spliced epitopes presented at the cell surface is a matter of substantial controversy (Liepe et al, 2016;Mylonas et al, 2018;Paes et al, 2019;Rolfs et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the genomics-based approach, which only provides for neoantigen prediction, mass-spectrometry allows us to take a real snapshot of the total MHC-bound protein interactome. Additionally, it could reveal not only neoantigens that originate from somatic mutation variants but also those which arise due to proteasome-mediated peptide splicing [ 157 , 158 ]. Using mass-spectrometry, it was shown that the proportion of spliced peptides relative to peptides displayed by HLA class I varies from 2-6% reported in [ 159 ] to 30% reported in [ 60 ].…”
Section: Mass Spectrometry-based Approachesmentioning
confidence: 99%